Assessing the effects of female protections on size structure and spawning potential in two clawed lobster fisheries subject to varying exploitation levels - Theberge, Kaitlyn; Sørdalen, Tonje K.; Pugh, Tracy L.; Kindsvater, Holly K. (bioRxiv, 2024)
Current fishery management practices in both the U.S. Gulf of Maine and Norwegian clawed lobster fisheries primarily focus on conserving mature females to maximize egg production. While abundance of adult American lobsters (Homarus americanus) in the Gulf of Maine remains high, declines appear to be on the horizon. Similarly, the European lobster (Homarus gammarus), is facing its lowest recorded population size in southern Norway. Understanding how management strategies and fishing practices impact lobster size structure and spawning potential could inform management to improve resiliency to climate-induced changes. In the Gulf of Maine fishery, egg-bearing (ovigerous) female lobsters are not only protected from harvest, but also v-notched which offers additional protection up to several years. Norway, however, protects egg-bearing females without v-notching. Comparing these fisheries allows us to test the effect of the different management practices and how they interact with key vital rates, including growth and natural mortality rates. We used deterministic size- and age-structured models and empirically estimated growth and molt functions to simulate relative changes in abundance, size structure, egg production, and sex ratios in response to these two female protection strategies. Our findings suggest that in all scenarios, controlling total fishing effort to low or moderate levels - relative to the F > 1 that has been estimated for American lobster - is most important for the effectiveness of size-based restrictions on harvest of larger individuals. Both forms of female protection enhance overall egg production in both species across levels of fishing intensity, but also result in a skewed sex ratio in favor of females and a more pronounced size disparity between female and male lobsters. Moreover, our results suggest that American and European lobster populations exhibit differential responses to the management strategies, likely due to variations in estimates of natural mortality rates and growth rates. Our results highlight the sensitivity of management effectiveness to assumptions regarding the underlying biology, but also provide a clear message that current intense fishing practices have likely depleted the ability of both species to compensate for fishing mortality in the long term.